ASPECTS OF HIGHLIGHTING THE ESSENCE OF SPEECH - Aitbayev Dilshodxuja Temirbayevich (Scholar Express Journal, 2024)
This article discusses the life of language in action, communication process, extralinguistic factors. At the same time, it is necessary to take into account syntactic, semantic, and logical aspects when clarifying the essence of a sentence, that, like any language unit, a sentence is a two-sided unit, it has both an expression and a content side, and the essence of syntactic units it is said that along with the semasiological approach, the onomasiological approach is also important in learning.
Keywords: sign system; means of communication; extralinguistic factors